SOCI 403-500: SOCIOLOGY OF MEXICAN AMERICANS - Murguia, Edward (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
I have two major objectives for this course. The first, is for you to become familiar with literature in the field of the Sociology of Mexican Americans. This includes knowing contemporary issues and problems as identified by scholars in the field and learning some of their research findings. My second major course objective is to engage you in critical thinking related to social issues regarding this field of study. This means learning the pros and cons surrounding issues in the Sociology of Mexican Americans. Even if you decide to stay with your original opinion on a subject, your opinion will now have become an informed opinion; one with greater sophistication and one that will serve you better in the years to come.